Block cipher four implementation on field programmable gate array - Kurniawan, Yusuf; Rizqulloh, Muhammad Adli (Communications in Science and Technology, 2020)
Block ciphers are used to protect data in information systems from being leaked to unauthorized people. One of many block cipher algorithms developed by Indonesian researchers is the BCF (Block Cipher-Four) - a block cipher with 128-bit input/output that can accept 128-bit, 192-bit, or 256-bit keys. The BCF algorithm can be used in embedded systems that require fast BCF implementation. In this study, the design and implementation of the BCF engine were carried out on the FPGA DE2. It is the first research on BCF implementation in FPGA. The operations of the BCF machine were controlled by Nios II as the host processor. Our experiments showed that the BCF engine could compute 2,847 times faster than a BFC implementation using only Nios II / e. Our contribution presents the description of new block cipher BCF and the first implementation of it on FPGA using an efficient method.